STATUS HUKUM PENJELASAN UNDANG-UNDANG BERDASARKAN SISTEM PERATURAN PERUNDANG-UNDANGAN INDONESIA - Septian, Ilham Fajar; Abdurahman, Ali (Jurnal Hukum & Pembangunan, 2021)
The law explanationis interpretation of norms contained in the body of the law. However, its existence as part of the law promulgatesthe unclear status of the lawexplanation as a mere interpretation or also as a binding legal norm. This has been further emphasized by the Constitutional Court Decision whichchanges its stance in judicial review to the law explanation. Therefore, issues regarding the legal status of the law explanationand the extent to which the Constitutional Court can judicial review tothe law explanationneed to be resolved. This research is a normative juridical research through literature study with historical, statutory, case, conceptual, and legal comparison approaches to secondary data in the form ofprimary and secondary legal materials which are analyzed descriptively qualitatively.